The Correlation of Predicting and Visualizing Strategies with Students’ Reading Comprehension at Junior High School - Fikhi Prayogo Wicaksono; Abdur Rosyid (Retain: Journal of Research in English Language Teaching, 2026)
Reading comprehension is a key component of English language learning, yet many students continue to experience difficulties in understanding written texts. Among the various reading strategies, predicting and visualizing have been widely recognized for promoting active engagement during reading. This study investigated the relationships between predicting and visualizing strategies and reading comprehension among eighth-grade students at a junior high school in Surabaya. A quantitative correlational design was employed involving 38 participants. Data were collected using a ten-item reading strategy questionnaire and a reading comprehension test based on narrative texts. Descriptive statistics, Pearson correlation, and one-way analysis of variance (ANOVA) were used to analyze the data. In answer to the first research question, the results indicated positive but non-significant relationships between predicting and reading comprehension (r = .227, p = .170) and between visualizing and reading comprehension (r = .308, p = .060). A significant positive relationship was found between predicting and visualizing strategies (r = .562, p < .001), suggesting that students who frequently employed one strategy also tended to use the other. In answer to the second research question, although the ANOVA showed no significant differences in reading comprehension across the four strategy-use groups (F(3, 34) = 2.638, p = .065), participants who reported using both strategies achieved the highest mean comprehension scores. Because the present study involved a relatively small and uneven sample, replicating the research with a larger group of participants would help clarify the role of predicting and visualizing in EFL reading comprehension.